Analysis of Viewing Learning Model in Class 5 of SD IT Muhammadiyah Bandongan Magelang District - Devita Indah Puspitasari; Arif Wiyat Purnanto (Edumaspul: Jurnal Pendidikan, 2023)
This study discusses the viewing learning model. The purpose of this research is to determine the presence of the viewing learning model in the 5th grade of Muhammadiyah Bandongan Elementary School IT. The type of research conducted is qualitative research with a natural observation approach. Data collection methods were carried out by being a shadow teacher, followed by observation, interviews, and field notes conducted for one month at the research site. The results of the study show that the viewing learning model is divided into several categories. The first is visual literacy, and the second is critical viewing. Based on the observation results, there are 10 viewing activities that occurred over a period of 37 days. In the 5th grade of Muhammadiyah Bandongan Elementary School IT, language reading and viewing activities accounted for 14%, which means it exceeded half of the 25%. This proves that the implementation of the viewing learning method is already being applied in the 5th grade of Muhammadiyah Bandongan Elementary School IT. The viewing learning model is implemented in several subjects, including Indonesian language, mathematics, science, social studies, arts and crafts, and physical education. This study emphasizes that the use of the viewing learning model plays an important role in enhancing students' visual literacy. Through the appropriate approach, students can develop a deep understanding of visual messages.